Dural Cells Release Factors Which Promote Cancer Cell Malignancy and Induce Immunosuppressive Markers in Bone Marrow Myeloid Cells. Issue 6 (15th February 2018) - Szerlip, Nicholas J; Calinescu, Alexandra; Smith, Eleanor; Tagett, Rebecca; Clines, Katrina L; Moon, Henry H; Taichman, Russell S; Van Poznak, Catherine H; Clines, Gregory A
Abstract: BACKGROUND: Thirty per cent of cancer patients develop spine metastases with a substantial number leading to spinal cord compression and neurological deficits. Many demonstrate a propensity toward metastasis to the posterior third of the vertebral body. The dura, the outer layer of the meninges, lies in intimate contact with the posterior border of the vertebral body and has been shown to influence adjacent bone. The effects of the dura on bone marrow and cancer cells have not been examined. Understanding the biology of spinal metastasis will provide insights into mechanisms of cancer growth and allow for new treatment strategies. OBJECTIVE: To examine the extent to which dura influences bone marrow/tumor cell metastatic characteristics. METHODS: Dura conditioned media (DCM) from primary dura was examined for the ability to stimulate tumor cell proliferation/invasion and to alter bone marrow cell populations. RNA sequencing of dural fibroblasts was performed to examine expression of cytokines and growth factors. RESULTS: DCM induced a significant increase in invasion and proliferation of multiple tumor cell lines, and of patient-derived primary spinal metastatic cells. DCM also increased the proliferation of bone marrow myeloid cells, inducing expression of immunosuppressive markers. RNA sequencing of dural fibroblasts demonstrated abundant expression of cytokines and growth factors involved in cancer/immune pathways. CONCLUSION: Factors released by primary dural cells induce proliferation of tumor cells and alter bone marrow to create a fertile environment for tumor growth. The dura therefore may play an important role in the increased incidence of metastases to adjacent bone.